565 Reflection on a Case of Dopamine-Responsive Dystonia. (October 2012) - Neamtu, ML; Dobrota, L
Abstract : Background: Characteristic symptoms of Dopamine-responsive dystonia (DRD) are increased muscle tone and Parkinsonian features. Children with DRD are often misdiagnosed. The disorder responds well to treatment with Levodopa. Aim: To reflect on a case of DRD. Method: Case report of a 13 years old girl misdiagnosed with tetany. Results: The girl was hospitalized for opisthotonus, positive Trousseau and Chvostek signs, diagnosed as tetany. The laboratory analysis have shown: normal serum of calcium (2.28 mmol/l), normal serum of magnesium (0.80 mmol/l), normal serum of phosphor (1.26 mmol/l), normal alkaline phosphatase (261 u/l) and normal PTH (27.9 pg/ml). Although the initial evolution was favorable (with intravenous calcium gluconate), the hypoparathyroidism diagnosis requiring reconsideration. The final diagnosis was DRD with long good evolution after Levodopa treatment. Referring to family history we learned that the patient have a cousin with the same symptoms. Conclusions: The misdiagnosis results from the following similarities: increased muscle tone with opisthotonus, writer's cramp with Trousseau sign, facial dystonia with Chvostek sign and difficult speech (due to facial dystonia) with patient illiteracy. All these similarities delayed the DRD diagnosis.